2013
DOI: 10.26719/2013.19.5.465
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of high risk pregnancy in Sousse, Tunisia

Abstract: RÉSUMÉ la présente étude descriptive a évalué la fréquence de certains facteurs de risque pour la grossesse à haut risque chez les femmes de la région de Sousse. Elle a été menée du 15 février au 15 août 2005 auprès de l'ensemble des femmes ayant accouché au-delà de 28 semaines d'aménorrhée dans quatre maternités publiques et présentant au moins un facteur de risque. La collecte des données a été effectuée dans les 24 heures qui ont suivi l'accouchement à partir des dossiers obstétricaux et fiches de consultat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…We recorded 1667 risk factors among 524 with a risk pregnancy, an average of 3.2 risk factors per woman, much higher result than that of Bouafia Tunisia [10]. In this study we found that 92.0% of women had at least one risk factor.…”
Section: Discussionmentioning
confidence: 53%
“…We recorded 1667 risk factors among 524 with a risk pregnancy, an average of 3.2 risk factors per woman, much higher result than that of Bouafia Tunisia [10]. In this study we found that 92.0% of women had at least one risk factor.…”
Section: Discussionmentioning
confidence: 53%
“…High-risk pregnancy is characterized by a high incidence of complications to the mother and/or the fetus during labor or in the postpartum which require specialized care [1]. The frequency of high-risk pregnancy ranges from 25.6 to 63.5% [28] with about 216 maternal deaths per 100,000 births [9]. The leading causes of death include cardiovascular disease, preeclampsia or eclampsia, haemorrhage, venous thromboembolism, and amniotic embolism [10].…”
Section: Introductionmentioning
confidence: 99%
“…The leading causes of death include cardiovascular disease, preeclampsia or eclampsia, haemorrhage, venous thromboembolism, and amniotic embolism [10]. Non-singleton pregnancies, diabetes mellitus, arterial hypertension and pre-eclampsia [2, 7, 9] are risk factors for complicated pregnancies, especially in the third trimester, and harm to newborns [3]. The third trimester of pregnancy is associated with worsening of pre-existing chronic comorbidities, obstetric complications, and drug administration [11].…”
Section: Introductionmentioning
confidence: 99%
“…The classification of high-risk pregnancies include maternal underlying disease, socioeconomic factors, the history of risk factors in previous pregnancies and the risk factors associated with the current pregnancy that may occur during it [17]. The prevalence of high-risk pregnancies varies from country to country, for example, in northern India, it is 31.4% [18] and in Tunisia -59.5% [19]. Moreover, it is reported that the prevalence of high-risk pregnancies varies in different regions of Iran [20].…”
Section: Introductionmentioning
confidence: 99%